Pemanfaatan Automatic Wastafel Portable (Awp) Yang Cerdas Dan Ramah Lingkungan Sebagai Pengaplikasian Perilaku Hidup Bersih Dan Sehat - Dahlia Kesuma Dewi; Mohd. Koginta Lubis (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Tjut Nyak Dhien, 2024)
This study aims to improve hygiene practices at Madrasah Ibtidaiyah Swasta Insan Ikhlas Islamic School by implementing an environmentally-friendly, sensor-based Automatic Portable Sink (APS). Initial observations showed that the school’s hand-washing facilities did not meet health standards, particularly in terms of hygiene and contact reduction. The proposed solution is a no-touch APS designed to facilitate hygienic hand-washing and reduce bacterial spread among students. The method used includes socialization, guidance, and demonstration of APS usage in the school environment, with monitoring of students’ hygiene behavior changes. The results show that APS effectively raises awareness and improves hand-washing practices among students while contributing to a cleaner school environment. Additionally, this eco-friendly APS reduces soap waste that could otherwise pollute surrounding areas. This innovation is expected to be replicable in other educational institutions to support good sanitation practices and meet health standards in educational settings.